Edukasi Cuci Tangan dan Pemeriksaan Telur Cacing Pada Kuku Tangan Siswa SD Inpres Pampang 1 Makassar - Rafika, Rafika; Alang, Hasria; Hartini, Hartini (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2020)
Intestinal worm disease is one of the parasitic diseases that still infect humans, especially children. School-age children, especially elementary school children, are generally less familiar with self-sanitation. Most diseases of the worms are transmitted through dirty hands. Community service at SD Inpres Pampang 1 was done to educate students about the implementation of good self-sanitation and precisely how to wash hands based on WHO standards. The tools used in this study were chalkboard, camera, microscope, reaction tube, glass object, glass cover, container/basin, stirrer rod, glass beaker, tube rack, petri dish, nail clippers, and pens. The materials used in this training were hand nails students SD Inpres Pampang 1, water, and salt. Based on the results and evaluation, it concludes 1) Worm infections can occur when there are worm eggs attached to the nails that are swallowed in with food. 2) improving participants ' understanding and knowledge of self-sanitation for everyday life, especially the right-hand washing way.